Implementation Of Aquaponic-Based Smart Greenhouse For Sustainable Agriculture Development In Nagari Parambahan, Bukit Sundi, Solok - Wellyalina, Wellyalina; Awalina, Rahmi; Erona, Meisilva; Pratama Eka Putra, Satria; Ismail, Ikhsan (Institute of Research And Community Service, Andalas University / LPPM Universitas Andalas, 2024)
Nagari Parambahan, located in Bukit Sundi District, Solok Regency, West Sumatra, has tremendous natural and cultural potential, but it still confronts obstacles in employing contemporary technologies for the benefit of the community. Using eco-friendly technologies, the Smart Green House design is suggested as a way to boost agricultural productivity. The urgency of this program is to empower the community with contemporary agricultural technology, which is predicted to boost agricultural production as well as economic and social wellbeing. In addition, the importance of education on sustainable agriculture is also a major focus, intending to preserve the environment. In the implementation of this Smart Green House, the aquaponics system is also introduced as an innovative technology that combines fish and plant farming in one integrated system. Aquaponics not only significantly reduces land and water usage, but also provides higher quality agricultural produce by utilizing fish waste as plant nutrients. By utilizing this technology, farmers can optimize production with higher efficiency, in line with the principles of sustainable agriculture. The program's objectives include increasing the utilization of modern technology in agriculture, empowering communities with agricultural technology knowledge and skills, and increasing agricultural production and economic welfare. The program also focuses on education about sustainable agriculture and forming a better community personality through empowerment. The targeted outputs of this program are the implementation of a functioning and useful Smart Green House, increased community knowledge and skills in modern agricultural technology, and a significant increase in agricultural yields. This program is also expected to be a model that can be applied in other areas. With collaboration and support from various parties, this program has the potential to provide great benefits to the people of Nagari Parambahan and become an example for other regions in utilizing agricultural technology for community welfare.